VITAMIN D TOPIKAL PADA PSORIASIS: SEBUAH TELAAH SISTEMATIK (PERDOSKI, 2020)
First line therapy for mild to moderate plaque psoriasis is topical therapy. Topical corticosteroids are first line therapy for psoriasis, but it has many side effects. Topical vitamin D is an alternative sparing therapy topical corticosteroid for psoriasis. Purpose to review various studies on the effects of topical vitamin D monotherapy for psoriasis. Literature search through PubMed and Science direct for published articles within the past 10 years. Analysis follows inclusion and exclusion criterias. Articles are included if it reviews the effectivity of topical vitamin D as monotherapy for psoriatic lesions. Review includes 13 randomized controlled trials, involving 8.391 psoriasis patients. Clinical evidences show therapeutic effects of topical vitamin D for psoriasis. Ointment as vitamin D vehicles has better penetration. Effectivity of topical vitamin D as monotherapy is inferior when compared with combined therapy or corticosteroid combination. Long term monotherapy with topical vitamin D has minimum side effects.